2019
DOI: 10.3390/cancers11030349
|View full text |Cite|
|
Sign up to set email alerts
|

A Feedback Loop Formed by ATG7/Autophagy, FOXO3a/miR-145 and PD-L1 Regulates Stem-like Properties and Invasion in Human Bladder Cancer

Abstract: Programmed cell death protein 1 (PD-1) and its ligand PD-L1 blockade have been identified to target immune checkpoints to treat human cancers with durable clinical benefit. Several studies reveal that the response to PD-1-PD-L1 blockade might correlate with PD-L1 expression levels in tumor cells. However, the mechanistic pathways that regulate PD-L1 protein expression are not understood. Here, we reported that PD-L1 protein is regulated by ATG7-autophagy with an ATG7-initiated positive feedback loop in bladder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 65 publications
(78 reference statements)
0
21
0
Order By: Relevance
“…To date, there are no clear proofs of miR-145 to target FGFR3 expression [ 26 ], but the revealed correlation needs further investigation. It might be of great importance taking into consideration Zhu and co-authors recent findings of a positive feedback loop for promoting PD-L1 expression in human bladder cancer cells via the ATG7/autophagy/FOXO3A/miR-145 axis [ 27 ]. Beside intergroup differences, it was of great importance to evaluate the markers prognostic value for patients’ survival.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there are no clear proofs of miR-145 to target FGFR3 expression [ 26 ], but the revealed correlation needs further investigation. It might be of great importance taking into consideration Zhu and co-authors recent findings of a positive feedback loop for promoting PD-L1 expression in human bladder cancer cells via the ATG7/autophagy/FOXO3A/miR-145 axis [ 27 ]. Beside intergroup differences, it was of great importance to evaluate the markers prognostic value for patients’ survival.…”
Section: Discussionmentioning
confidence: 99%
“…The whole-cell extracts were then prepared, as described in the previous studies 51, 52. Cell extracts were subjected to western blot analysis, as previously described 53 . The images were acquired by scanning with the phosphor imager (Typhoon FLA 7000, GE Healthcare).…”
Section: Methodsmentioning
confidence: 99%
“…35 Zhu et al . 36 indicated that PD-L1 was one of the downstream targets of ATG7. PD-L1 is a co-inhibitory transmembrane protein that allows cancer cells to escape from the immune system.…”
Section: The Relationship Between Autophagy and Tumorsmentioning
confidence: 99%